2016
DOI: 10.1515/jtes-2016-0006
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Intervention for Developing Long-Term Health Literacy of Individuals: Possibilities and Limitations

Abstract: Web-based interventions (WBI) are purposefully developed online programs designed for wide range of users (clients, patients, health care specialists, as well as medical practitioners) which allow obtaining and using information on various issues related to health maintenance and improvement.On the basis of the analysis of scientific literature, the article provides an overview of WBI types and components, as well as a structural model of WBI and its user in the context of environment factors. The possibilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Web-based patient education has been proven to increase patients' knowledge and satisfaction in several fields, 24,25 including that of health literacy. 26 However, there seems to be a gap in the research on web-based educational interventions in the context of drug utilization. It has been suggested that non-web-based educational interventions could have positive effects on knowledge about medications.…”
Section: Benefits Of Web-based Educational Interventionsmentioning
confidence: 99%
“…Web-based patient education has been proven to increase patients' knowledge and satisfaction in several fields, 24,25 including that of health literacy. 26 However, there seems to be a gap in the research on web-based educational interventions in the context of drug utilization. It has been suggested that non-web-based educational interventions could have positive effects on knowledge about medications.…”
Section: Benefits Of Web-based Educational Interventionsmentioning
confidence: 99%